The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/0333102414563088
|View full text |Cite
|
Sign up to set email alerts
|

Auditory hallucinations associated with migraine: Case series and literature review

Abstract: Paracusias uncommonly co-occur with migraine and usually feature human voices. Their timing and high prevalence in patients with depression may suggest that paracusias are not necessarily a form of migraine aura, though could be a migraine trait symptom. Alternative mechanisms include perfusion changes in primary auditory cortex, serotonin-related ictal perceptual changes, or a release phenomenon in the setting of phonophobia with avoidance of a noisy environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…In one series, some patients also reported gustatory hallucinations, but little information was presented regarding the duration and temporal profile of the symptoms . A retrospective review of auditory hallucinations reported to occur with migrainous headaches found that the hallucinations usually featured human voices, never preceded a headache, had a widely variable duration from less than 5 minutes to constantly present, and often occurred with comorbid psychiatric disorders, suggesting that they were not a form of migraine aura . If olfactory, gustatory, or auditory hallucinations are reported by patients in the context of their migrainous headaches, alternative causes, specifically epilepsy and psychiatric disorders, should be considered.…”
Section: Olfactory Gustatory and Auditory Hallucinationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In one series, some patients also reported gustatory hallucinations, but little information was presented regarding the duration and temporal profile of the symptoms . A retrospective review of auditory hallucinations reported to occur with migrainous headaches found that the hallucinations usually featured human voices, never preceded a headache, had a widely variable duration from less than 5 minutes to constantly present, and often occurred with comorbid psychiatric disorders, suggesting that they were not a form of migraine aura . If olfactory, gustatory, or auditory hallucinations are reported by patients in the context of their migrainous headaches, alternative causes, specifically epilepsy and psychiatric disorders, should be considered.…”
Section: Olfactory Gustatory and Auditory Hallucinationsmentioning
confidence: 99%
“…At present, there are more data supporting a cortical neuroanatomical basis for migraine related dizziness . Rarely, migraine can present in association with auditory, olfactory, and gustatory hallucinations . However, given the infrequency of these events, other causes should be investigated as both seizures and stroke have been associated with cortical spreading depression and migrainous headaches …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Migraine aura is one of the most obvious sensory phenomena associated with migraine: a sensory hallucination preceding the onset of the headache itself, which can be in any modality, but is most commonly visual (Steiner et al, 2003). Other hallucinations reported include vestibular and auditory (Cal and Bahmad, 2008), auditory and olfactory (Miller et al, 2015). There is also osmophobia (sensitivity to smells) reported during the migraine attack and 84% of individuals reporting olfactory hallucinations have migraine (Coleman et al, 2011).…”
Section: A Brief Consideration Of Unimodal Sensory Differences In Migmentioning
confidence: 99%
“…Metamorphopsia, in which objects appear larger or smaller than they actually are, characterizes Alice in Wonderland syndrome. Ringing in ear, auditory hallucination, and sudden hearing loss are uncommon [26][27][28], but they can present in isolation or cooccur with migraine. In the presence of atypical aura, a diagnosis of migraine like syndromes should be explored.…”
Section: Atypical or Non-conventional Auramentioning
confidence: 99%